Using Wood Ash as Superfine Additive and Air Bubble Stabilizer in Foam Concrete - Alhakem, Ritta (Latakia University Journal -Engineering Sciences Series, 2025)
Technological development has led to the emergence of many modern construction techniques in recent decades, which achieve the engineering specifications required in construction with the best quality, lowest cost and greatest durability. As a result of the war that Syria witnessed, which led to the destruction of many buildings, facilities and infrastructure, the demand for building materials and the use of cement has increased, which is this necessitated thinking about finding a solution to secure these resources and searching for alternative building materials, At the same time, focusing on the principle sustainability and achieving its standards, therefor it was necessary to introduce new alternatives to the building materials used in the production of concrete, and an attempt to localize this technology in local industries. One of the common wastes that this research focused on is wood ash which has been used as a cement additive material in the manufacture of foamed concrete with varying mechanical specifications, and a low apparent density that reached to 720Kg/m3 in some compositions, which is considered an important factor in achieving thermal and sound insulation, and a significant reduction of the mechanical load on the structural elements. The preliminary results of this research showed the possibility of manufacturing samples of foamed concrete with an apparent density ranging between 728 and 974Kg/m3, with a homogeneous appearance and mechanical resistance that achieves the values specified by international specifications, with the possibility of increasing them by making modifications to the designs.